(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: The aim of this study was to document the pattern of foreign bodies in the nose, their treatment and outcome. Patients and Methods: This was a prospective audit of all children seen in the Department of ENT, Head and Neck surgery, PGMI/LRH Peshawar Pakistan, from Jan. 2011 to Dec. 2011. All the patients fulfilling the inclusion criteria were properly evaluated in terms of detailed history, thorough examination and appropriate investigations. Data was analyzed using SPSS version 17. Results: Of a total of 173 patients with ear, nose and throat foreign bodies seen during the study period, 71 patients had foreign bodies in the nose. The male/female ratio was 1.5:1 and the mean age was 2.5 years (range 1-15 years), under-5s comprising 72% of the patients. The most common foreign bodies were grains and seeds (35%). Most of the foreign bodies (89%) were mechanically extracted. In 61% of cases removal was done by a Senior Registrar. General anaesthesia was needed in a minority of cases. Minimal epistaxis after removal occurred in 50.7%, and only 1 patient had septal perforation. Conclusion: Nasal foreign bodies are still a challenge among children under 5 years of age. Public health education is needed to make parents and caregivers aware that it is hazardous for a child to insert a foreign body into the nose. With adequate training, primary healthcare practitioners can manage most cases successfully and will know when to refer complicated ones.